Workload, Stress, and Motivation as Key Drivers of Employee Performance: Beban Kerja, Stres, dan Motivasi sebagai Faktor Utama yang Mempengaruhi Kinerja Karyawan - Safenda, Anggit Rahmaddani; Kirana, Kusuma Chandra; Septyarini, Epsilandri (Academia Open, 2025)
General Background: Employee performance is a key determinant of organizational success, particularly in public service institutions. Specific Background: At the Social Service Office of Gunungkidul Regency, performance optimization is essential to meet increasing administrative and social demands. Knowledge Gap: While previous studies have addressed individual factors such as workload, stress, or motivation, limited research integrates these variables simultaneously within local government contexts in Indonesia. Aims: This study aims to examine the influence of workload, work stress, and work motivation on employee performance—both individually (partially) and collectively (simultaneously). Results: Using a quantitative ex post facto design with total sampling of 45 civil servants and contract workers, data were collected via validated and reliable Likert-scale questionnaires. Multiple linear regression analysis revealed that workload, work stress, and motivation each have a positive and significant effect on performance. Notably, moderate work stress (eustress) enhances alertness and discipline. Collectively, the three variables account for 82.5% of the variance in employee performance. Novelty: The study highlights the constructive role of moderate stress in public service performance, a nuance often overlooked in stress-performance literature. Implications: These findings suggest that managing optimal levels of workload, stress, and motivation is critical to enhancing public sector employee performance. Highlights: Balanced stress (eustress) can enhance employee effectiveness. Motivation significantly drives public service performance. Combined variables explain 82.5% of performance outcomes. Keywords: Workload, Work Stress, Work Motivation, Employee Performance, Public Sector